2009
DOI: 10.1007/s10979-008-9143-y
|View full text |Cite
|
Sign up to set email alerts
|

Outsmarting the liars: The benefit of asking unanticipated questions.

Abstract: We hypothesised that the responses of pairs of liars would correspond less with each other than would responses of pairs of truth tellers, but only when the responses are given to unanticipated questions. Liars and truth tellers were interviewed individually about having had lunch together in a restaurant. The interviewer asked typical opening questions which we expected the liars to anticipate, followed by questions about spatial and/or temporal information which we expected suspects not to anticipate, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
287
6
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(309 citation statements)
references
References 32 publications
11
287
6
5
Order By: Relevance
“…As a consequence, behavioural indicator methods for security screening necessarily comprise a rigid procedure in which the kinds of indicators to look for are prescribed and trained. The scripted nature of a suspicious signs interview makes it difficult to employ psychologically validated techniques such as tactical use of evidence (Dando et al, 2012), tests of expected knowledge , and unexpected questions (Vrij et al, 2009). Intuitive processing in deception detection of the kind promoted by a suspicious signs approach exacerbates truth and lie biases in deception judgements (Meissner & Kassin, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, behavioural indicator methods for security screening necessarily comprise a rigid procedure in which the kinds of indicators to look for are prescribed and trained. The scripted nature of a suspicious signs interview makes it difficult to employ psychologically validated techniques such as tactical use of evidence (Dando et al, 2012), tests of expected knowledge , and unexpected questions (Vrij et al, 2009). Intuitive processing in deception detection of the kind promoted by a suspicious signs approach exacerbates truth and lie biases in deception judgements (Meissner & Kassin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, asking unanticipated questions during interviews has been shown to raise the cognitive load of deceivers more than truth-tellers, leading to higher detection rates (Vrij et al, 2009). …”
Section: Approaches To Detecting Deceptionmentioning
confidence: 99%
“…Liars may have an easier task and, hence, provide more detailed answers, if they are asked questions that they are prepared for. In support of the unexpected-questions approach, it has been found that more pronounced differences between truth tellers and liars appeared in answers to unexpected questions than in answers to expected questions (Roos af Hjelmsäter, Öhman, Granhag, Sooniste, Granhag, Knieps, & Vrij, 2013;Vrij et al, 2009;Warmelink, Vrij, Mann, Jundi, & Granhag, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Despite these issues, some valid cues have been discovered that, on average, do distinguish deceptive from honest individuals. Each cue can be assigned to the category of a verbal (or content), a paraverbal, or a nonverbal cue (Hart, Fillmore, & Griffith, 2010;Sporer & Schwandt, 2006 (Newman, Pennebaker, Berry, & Richards, 2003); use fewer exclusive words (e.g., "except"; Newman et al, 2003); reveal details of poorer quality and quantity directly after an event (DePaulo et al, 2003;Granhag et al, 2003;Vrij, 2004;Vrij, Akehurst, Soukara, & Bull, 2004;Vrij, Edward, Roberts, & Bull, 2000;Vrij, Leal, Granhag, Mann, Fisher, Hillman, & Sperry, 2009;Vrij et al, 2008); include fewer spontaneous corrections (Vrij et al, 2004;Vrij et al, 2000); include less contextual embedding Vrij et al, 2000); are more consistent in statements made over time (Strömwall & Granhag, 2003a); include fewer reproductions of conversations Vrij et al, 2000); use more cognitive operations in their speech ; produce less plausible accounts of events (DePaulo et al, 2003); produce accounts that are less logical (DePaulo et al, 2003); be more likely to include discrepant or ambivalent content (DePaulo et al, 2003); appear less expressive (DePaulo et al, 2003, Vrij, 2000; appear more passive (DePaulo et al, 2003, Vrij, 2000; seem less confident (DePaulo et al, 2003, Vrij, 2000; be less involved in conversation (DePaulo et al, 2003, Vrij, 2000; appear more tense (DePaulo et al, 2003, Vrij, 2000; be less cooperative (DePaulo et al, 2003…”
Section: Purported Versus Valid Cues Used To Detect Deceptionmentioning
confidence: 99%
“…Fortunately, when trained in empirically-based methods, legal professionals can improve their deception detection abilities (Vrij et al, 2009). A meta-analysis of training techniques used prior to 2003 found that training resulted in small but dependable, positive gains in lie detection (Frank & Feeley, 2003).…”
Section: Purported Versus Valid Cues Used To Detect Deceptionmentioning
confidence: 99%